High-risk neuroblastoma in Mexico: from multimodal treatment to immunotherapy. Regarding the first case treated with naxitamab - Olaya Vargas, Alberto; Salazar-Rosales, Haydee; Caballero-Palacios, Marcela; Ramírez-Uribe, Nideshda; López-Hernández, Gerardo; Morales-Martinez, Erika; Cervantes-Delgado, María; Velasco Hidalgo, Liliana; Castellanos-Toledo, Araceli; Cárdenas-Cardos, Rocío; Niembro-Zúñiga, Ana; Rivera-Luna, Roberto; et al. (Frontiers in Oncology, 2025)
IntroductionWe report herein the case of a patient diagnosed with high-risk neuroblastoma (HR-NB), treated with naxitamab following suboptimal response to induction chemotherapy, becoming the first patient to receive this therapy at the National Institute of Pediatrics (INP) in Mexico. We discuss the clinical course, therapeutic approach, response to treatment, adverse events, and fatal outcome, focusing on the implications of immunotherapy access in low- and middle-income countries (LMIC).Case presentationA 2-year-old male presented with a 3-month history of a left front-temporal mass and left-sided exophthalmos. Magnetic resonance imaging (MRI) revealed a poorly defined retroperitoneal and paravertebral mass, and a destructive cranial lesion involving the sphenoid wing and the orbit. PET-CT and MIBG scans confirmed widespread metastatic disease in bone, orbit, and intracranial structures, consistent with stage 4 neuroblastoma. Histopathology of a cranial biopsy confirmed poorly differentiated neuroblastoma. The patient was classified as high-risk based on age and metastatic disease, and underwent multimodal treatment including chemotherapy, partial tumor resection, radiotherapy, and anti-GD2 immunotherapy with naxitamab under protocol HITS-17-251. After five cycles, imaging showed complete response in cranial metastases. Adverse events during immunotherapy were mild (Grade I–II), including erythema, pruritus, urticaria, and transient hypotension, all managed with antihistamines and IV fluids. However, one month after the final cycle, the patient developed sudden neurological deterioration with cerebral edema and hydrocephalus. Despite intensive care, he progressed to brain death, with neurotoxicity suspected as the cause.DiscussionThe primary objective of implementing novel immunotherapeutic strategies, in addition to improving event-free survival (EFS) and overall survival (OS) in patients diagnosed with high-risk neuroblastoma, is to reduce adverse effects and lower both short- and long-term mortality. It is worth noting that the current cost of anti-GD2 therapies available in Latin America is estimated to exceed $450,000 USD. In a country like Mexico, where the minimum daily wage is approximately $10 USD, access to these therapies remains unattainable for the majority of the population. Therefore, it is essential to highlight the importance and substantial clinical impact of immunotherapy on survival outcomes in patients with refractory neuroblastoma. This recognition should support advocacy for broader access to these therapies. Despite their high costs, the demonstrated benefits should outweigh the disadvantages, justifying efforts to make them accessible to all patient populations.ConclusionsFuture studies in LMICs including Mexico and Latin America, must focus on optimizing dosing strategies to minimize adverse effects and improve both survival outcomes and the quality of life for patients receiving immunotherapy.